2013
DOI: 10.1016/j.jconrel.2013.06.014
|View full text |Cite
|
Sign up to set email alerts
|

A new tool to ensure the fluorescent dye labeling stability of nanocarriers: A real challenge for fluorescence imaging

Abstract: Numerous studies on nanocarriers use fluorescent dye labeling to investigate their biodistribution or cellular trafficking. However, when the fluorescence dye is not grafted to the nanocarrier, the question of the stability of the labeling arises. How can it be validated that the fluorescence observed during an experiment corresponds to the nanocarriers, and not to the free dye released from the nanocarriers? Studying the integrity of the labeling is challenging. Therefore, an innovative approach to confirm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 32 publications
3
67
0
Order By: Relevance
“…We have previously shown that Nile Red (NR) leaks out of poly(butyl cyanoacrylate) (PBCA)-NPs upon cell contact (24), which is in line with various studies showing NR release from NPs (18,19,25,26). The hydrophobic analogue NR668 was found to leak much less than NR from nanoemulsions (NEs) (18), and to be suitable for tracing the PBCA-NPs, as it was not released from the NPs until they were endocytosed and degraded (12).…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…We have previously shown that Nile Red (NR) leaks out of poly(butyl cyanoacrylate) (PBCA)-NPs upon cell contact (24), which is in line with various studies showing NR release from NPs (18,19,25,26). The hydrophobic analogue NR668 was found to leak much less than NR from nanoemulsions (NEs) (18), and to be suitable for tracing the PBCA-NPs, as it was not released from the NPs until they were endocytosed and degraded (12).…”
Section: Introductionsupporting
confidence: 68%
“…NR has repeatedly been shown to leak out of various NPs (18,19,25,26), and we concluded in a previous study that NR was taken up by cells through contact-mediated transfer within minutes after addition of PBCA-NPs (24). The retention of a dye in a NP is largely governed by hydrophobic and electrostatic interaction between the dye and NP.…”
Section: Dye Retention and Leakage From Npsmentioning
confidence: 75%
See 1 more Smart Citation
“…The LUV size and zeta potential were not affected by the presence of DiD, confirming that the fluorophore, at that concentration, did not affect the assembly. 34 A LUV aliquot of 400 µL was intravenously delivered (caudal veins) to each rat. At various time points, from 5 min to 24 h following the injection, blood samples (about 400 µL) were collected.…”
Section: Luvs Characterization the Hydrodynamic Diameters Of The Luvmentioning
confidence: 99%
“…The pharmaco-kinetics was examined using DiD, a fluorescent lipophilic probe that labels the LUV walls and has, in general, limited transfer from labeled to unlabeled membranes. 34 AV-400 spectrometer operating at 400 MHz for 1 H. The diffusion measurements were carried out at 25 o C using a Bruker diffusion probe (Diff60) equipped with a 1 H/ 2 H 5-mm coil. This probe includes one gradient coil, along the z axis, capable of delivering magnetic field gradients up to 2900 G/cm.…”
Section: Introductionmentioning
confidence: 99%